Applications of eDNA Metabarcoding for Vertebrate Diversity Studies in Northern Colombian Water Bodies - Lozano Mojica, Juan Diego; Caballero, Susana (Frontiers in Ecology and Evolution, 2021)
Environmental DNA metabarcoding is a tool with increasing use worldwide. The uses of such technology have been validated several times for diversity census, invasive species detection and endangered/cryptic/elusive species detection and monitoring. With the help of this technology, water samples collected (n= 37) from several main rivers basins and other water bodies of the northern part of Colombia, including the Magdalena, Sinú, Atrato and San Jorge river basins, were filtered and analyzed and processed using universal 12s primers for vertebrate fauna and NGS. Over 200 native taxa were detected, the majority of them being fish species but also including amphibia, reptiles and several non-aquatic species of birds and mammals (around 78%, 3%, 2%, 9% and 8% respectively) Among the matches, vulnerable and endangered species such as the catfish Pseudoplatystoma magdaleniatum and the Antillean manatee (Trichechus manatus) were detected. The manual revision of the data revealed some geographical incongruencies in classification. No invasive species were detected in the filters. This is, to our knowledge, the first time this technique is used in the country and this tool promises to bring advances in monitoring and conservation efforts, since its low cost and fast deployment allows for sampling in small periods of time, together with the fact that it can detect a wide range of species, allows for a new way of censing the vertebrate diversity in Colombia. Diversity analysis showed how the species identified using this method point to expected community structure although still much needs to be improved in rates of detection and genomic reference databases. This technique could be used in citizen science projects involving local communities in these regions.